(untitled) (Nepalese Journal of Radiology, 2023)
Introduction: Bronchial artery embolization (BAE) is a minimally invasive interventional procedure, which is now considered the first-line management strategy and an alternative to surgery for massive and recurrent haemoptysis. The advances in embolic agents have led to a significant improvement in the success rates of the procedure, however, there has been no significant change in the recurrence rate of haemoptysis. Methods: This retrospective study was conducted at a tertiary care center from January 2012 to December 2020. The final analysis was performed on 123 patients [NBCA(n= 37) and PVA(n= 86)]. Technical and clinical success rates, complications and recurrence rates were compared between the two groups. Results: A total of 248 arteries were embolized. In the PVA group, clinical success was achieved in 84 out of 86 cases (97.6%) and with NBCA in 36 out of 37 patients (97.3%) (p >0.05). Of the 120 patients in whom BAE was clinically successful, recurrence was observed in 43 patients within the 12-month follow-up period. The study showed a statistically significant association between the embolizing agent used for BAE and the recurrence of hemoptysis (χ2 = 4.80, df = 1, p = 0.028). The use of PVA particles for BAE was found to have 2.62 times higher odds (95% CI 1.10 - 6.81) of recurrence of hemoptysis as compared to the use of NBCA glue. Conclusions: BAE with NBCA provided higher hemoptysis-free survival rates compared with PVA particles without increasing complication rates.